MODELLING FEAR OF ORAL PRESENTATION THROUGH SOCIAL COGNITIVE THEORY:AN APPLICATION OF PLS-SEM - Rahmat, Noor Hanim; Ibrahim, Nursuhaila (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This study investigates facets of fear of oral presentations among EFL university. Oral presentations are almost a compulsory requirement in higher education, yet many learners’ experience anxiety due to the simultaneous demands of content preparation and language proficiency across all courses. Guided by Social Cognitive Theory, this study predicts a model explaining the factors of oral presentation anxiety. This quantitative design used the PLS-SEM to address four research questions and test four corresponding hypotheses. Data was collected from 104 undergraduates enrolled in a Malaysian public university. The analysis showed that the null hypotheses for Hypothesis 1 and Hypothesis 3 were accepted, indicating no significant relationships between fear and personal factors, nor between and environmental factors. In contrast, behavioural components demonstrated a significant association with presentation anxiety. Additionally, findings for Research Question 4 revealed notable effects across personal, behavioural, and environmental components; effect sizes were substantial for personal and behavioural factors, while environmental influences also demonstrated a considerable impact. These results underscore the complexity of factors shaping oral presentation anxiety and highlight behavioural components as the most prominent predictors within the proposed model.